Noise sensitivity and its associated factors among the students of Rajshahi City in Bangladesh: A cross-sectional study - Sarker, Pramath Chandra; Ullah, Md. Nayamat; Morshed, Fahim; Sultana, Sabina; Siddique, Md. Nur-E-Alam (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: Noise pollution is an important environmental problem with far-reaching and unavoidable consequences. The present study aimed to identify noise sensitivity and its associated factors among students of Rajshahi City. Methods: A total of 473 respondents were selected conveniently from five educational institutions in Rajshahi City. Among them, 273 were women, and 200 were men aged 18 to 28 (mean, 22.9). The Bangla version of the Noise Sensitivity Scale was administered to measure the participants' noise sensitivity level. Results: Noise sensitivity varied significantly with sleep duration, anger toward noise polluters, level of noise annoyance, and the avoidance of noise-polluted roads (using alternative roads) among the respondents. There was no significant effect of sex or residence in a noise-polluted area on noise sensitivity. The results also indicate that anger at polluters and noise annoyance strongly influence noise sensitivity. Conclusion: Noise sensitivity affects many aspects of human life. These findings will assist policymakers, and urban planners mitigate the harmful effects of noise sensitivity on human health.